(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: To formulate a convergent and consensus expert panel to calculate normative drug cost in the top twenty diseases in primary care. Method: In the first round, the expert panel define a list of consensus statements based on data derived from non-systematic reviews of treatment standard for the top twenty disease in primary care. In the second round, experienced doctors in treatment at primary care were involved to express individual consent to the statements using questionnaire. Face-to-face meeting were held simultaneously with filling questionnaire. Consensus was defined as 75% agreement. Result: Delphi process at the first round, the expert panel consisting of 11 doctors in primary care defined a list of 60 statements from 20 diseases on the treatment standard calculated the normative cost of acute and chronic disease in primary care. The second round involved 11 doctors who are experienced in primary care with more than 6 years’ experience in doing treatment in primary care. Conclusion: The identified consensus statement can help doctors to apply the normative cost calculation results on the top 20 diseases in primary care as evidence based policy study material for calculating the percentage of drug cost in the capitation system in Indonesia. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 291-301